AN APPROACH TO MUSIC TEACHER AS MULTI-INSTRUMENTALIST - ALEKNAVIČIUS, Simas; URNIEŽIUS, Rytis (Studia Universitatis Babes-Bolyai Musica, 2020)
The necessity and possibilities of music teachers to acquire skills of playing several musical instruments is discussed in the current article. The advantages and challenges of multi-instrumentalists’ practice are analysed. The authors strive to determine the peculiarities of music teachers – multi-instrumentalists’ activities and the advantages of such kind of teachers in comparison with conventionally trained ones. The essential competences of music teachers trained to handle several musical instruments were distinguished and their work possibilities discussed. The analysis allowed to discern several advantages of music teacher multi-instrumentalist, such as ability to organize different ensembles in which they are able to play the necessary instrument or temporary replace one of the instruments; high competence to explain peculiarities and character of different musical instruments of symphony orchestra in their music lessons; advanced skills in writing arrangements or composing music for ensembles and soloists.